Conceptualising a university teaching practice in an activity theory perspective - Treffert-Thomas, Stephanie (NOMAD Nordic Studies in Mathematics Education, 2015)
In this article I present a theorisation of a university mathematics teaching practice, based on a research study into the teaching of linear algebra in a first year mathematics undergraduate course. The research was largely qualitative and consisted of data collected in interviews with the lecturer and in observations of his lectures. Using Leontiev’s (1981) activity theory framework I categorised the teaching of linear algebra on three levels: activity-motive, actions-goals and operations-conditions. Each level of analysis provided insights into the lecturer’s teaching approach, his motivation, his intentions and his strategies in relation to his teaching. I developed a model of the teaching process that relates goals as expressed by the lecturer in interviews to the strategies that he designed for his teaching.